AN ANALYSIS POSITIVE AND NEGATIVE STATEMENTS OF OPRAH WINFREY’S STATUS ON TWITTER - Aditya, Silvia Erlin; Asri, Ervi Mayang (JURNAL LITERARY CRITICISM, 2015)
This paper analyzed the positive and negative statements of Oprah Winfrey?s Status on Twitter. Status is the tweet of the Twitter users in order to communicate or broadcast what they are doing; their feelings, happiness, sorrow, and many other events that they feel can spread rapidly by using Twitter. Oprah Winfrey is an American media proprietor, talk show host, actress, producer, and philanthropist. Oprah?s status on twitter got positive response by her followers. Along she is a queen in talk show, she already develop good communication style and loss the obstacle between herself and audience. Winfrey often make status on her twitter to show her image. Beside make status about motivation, from her status on twitter, Oprah Winfrey also sometime publish her real life in her status on twitter. This thing be proved with some her status which is analyzed in this research. Oprah?s tweets also often contain about success tips and as motivation sentence. Based on the result of the research and it can be concluded that Oprah?s status on twitter more dominant positive than the negative one it is Because of her life is inspiring many people and Oprah Winfrey is famous celebrity and good or kind-hearted person public figure. Keyword : Analysis, Positive and negative sentence, Oprah Winfrey, Status, Twitter